Breaking News! Making and testing Bronze Age balance scales. (August 2020) - Hermann, Raphael; Steinhoff, Judith; Schlotzhauer, Philipp; Vana, Philipp
Highlights: Bronze Age balance scales had high load-bearing capacities. Bone balance beams were likely turned on a lathe. Nettle fibres provide excellent material for cord making. Abstract: This interdisciplinary paper (archaeology, macromolecular chemistry and material science) investigates the production and load-bearing capacities of Bronze Age balance scales. The existence of weighing equipment and practices in Late Bronze Age Europe has been proven beyond doubt. Although hundreds of balance weights from Central and Western Europe have recently been identified in the archaeological record, balance scales are still extremely rare. Consisting of balance beams, suspension cords, scale pans and sometimes metal suspension loops, the only evidence found to date are 18 complete and fragmented balance beams. Made of bone or antler, these balance beams are often perceived as extremely fragile and only able to weigh-out minute loads. This, however, had never been tested. In order to understand exactly how Bronze Age balances were made, of what materials and how much load they could bear, a number of replica balance beams, suspension cords and metal loops were created. The load-bearing capacity was then tested with two standard material sciences testing methods: three-point bending tests and uniaxial tensile testing.